Rao-blackwellised particle filtering via data augmentation - Andrieu, C; De Freitas, N; Doucet, A (Neural information processing systems foundation, 2002)
In this paper, we extend the Rao-Blackwellised particle filtering method t o more complex hybrid models consisting of Gaussian latent variables and discrete observations. This is accomplished by augmenting the models with artificial variables that enable us to apply Rao-Blackwellisation. Other improvements include the design of an optimal importance proposal distribution and being able to swap the sampling an selection steps to handle out liers. We focus on sequent ial binary classifiers t hat consist of linear- combinations of basis functions, whose coefficients evolve according t o a Gaussian smoothness prior. Our results show significant improvements.